One is not enough: Multiple views in a media space - Gaver, William; Sellen, Abigail; Heath, Christian; Luff, Paul (Proceedings of INTERCHI '93, Amsterdam, April 24-29, 1993)
Media spaces support collaboration, but the limited access they provide to remote colleagues’ activities can undermine their utility. To address this limitation, we built an experimental system in which four switchable cameras were deployed in each of two remote offices, and observed participants using the system to collaborate on two tasks. The new views allowed increased access to task-related artifacm indeed, users preferred these views to more typical “face-to-face” ones. However, problems of establishing a joint frame of reference were exacerbated by the additional complexity, leading us to speculate about more effective ways to expand access to remote sites.